2017
DOI: 10.1186/s13570-017-0101-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of self-help groups on pastoral women’s empowerment and agency: A study in Nigeria

Abstract: While women in pastoralist communities are key stakeholders in the production of milk and dairy products for income generation, they are largely ignored in other areas of development such as health. The need to involve women self-help groups, in pastoralist areas in both animal health and human health development programmes, is essential, particularly given the high incidence of zoonotic diseases in these communities (Maudlin I, Eisler MC and Welburn SC, Philosophical Transactions of the Royal Society B: Biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Eleven observational studies discussed women's empowerment in the context of control and use of income. Some evidence suggests that women may have more control over income from small ruminant, poultry, and dairy products ( 99 , 101 , 114 , 115 ). Some evidence suggests that as a livestock production activity becomes more lucrative, the dynamics of control between men and women change, with more control shifting to men ( 107 , 116 , 117 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eleven observational studies discussed women's empowerment in the context of control and use of income. Some evidence suggests that women may have more control over income from small ruminant, poultry, and dairy products ( 99 , 101 , 114 , 115 ). Some evidence suggests that as a livestock production activity becomes more lucrative, the dynamics of control between men and women change, with more control shifting to men ( 107 , 116 , 117 ).…”
Section: Resultsmentioning
confidence: 99%
“…Given the broad scope of concerns surrounding empowerment, scholars have examined many topics across a wide range of contexts [ 33 ]. Studies have examined many topics, including educational attainment [ 37 ], political participation [ 38 ], gender-based domestic violence [ 39 ], resource control [ 40 , 41 , 42 ], entrepreneurialism [ 43 ], well-being [ 44 ], household decision-making [ 45 , 46 , 47 ], time poverty [ 48 ], and health [ 49 , 50 ]. While women’s empowerment is intrinsically important, studies in developing countries have shown that empowering women can also improve children’s health and education [ 51 ], decrease child mortality [ 52 ], improve the organizational effectiveness of businesses [ 53 ], increase agricultural productivity [ 54 ], and increase economic growth and reduce poverty [ 55 ].…”
Section: Background Of the Studymentioning
confidence: 99%
“…146 Badejo describes how self-help groups led to positive empowerment changes for pastoralist women in Nigeria and Ibrahim argues that pastoralist women in Chad play dynamic, empowered roles in redefining Mbororo cultural identity. 147 Women in pastoralist communities do in some cases form and participate in economic associations or cooperatives (as has been noted in Guinea 148 and East Africa 149 ). To a minor degree, women pastoralists have even begun organizing at an international level -best exemplified by the 2010 Mera Declaration of the Global Gathering of Women Pastoralists, which included participants from Burkina Faso, Cameroon, Mali, and Niger among others.…”
Section: Gender Dimensions Of Governancementioning
confidence: 99%